Biodistribution and clearance of a filamentous plant virus in healthy and tumor-bearing mice. (February 2014) - Shukla, Sourabh; Wen, Amy M; Ayat, Nadia R; Commandeur, Ulrich; Gopalkrishnan, Ramamurthy; Broome, Ann-Marie; Lozada, Kristen W; Keri, Ruth A; Steinmetz, Nicole F
Aim: Nanoparticles based on plant viruses are emerging biomaterials for medical applications such as drug delivery and imaging. Their regular structures can undergo genetic and chemical modifications to carry large payloads of cargos, as well as targeting ligands. Of several such platforms under development, only few have been characterized in vivo . We recently introduced the filamentous plant virus, potato virus X (PVX), as a new platform. PVX presents with a unique nanoarchitecture and is difficult to synthesize chemically.Methods: Here, we present a detailed analysis of PVX biodistribution and clearance in healthy mice and mouse tumor xenograft models using a combination of ex vivo whole-organ imaging, quantitative fluorescence assays and immunofluorescence microscopy.Results & conclusion: While up to 30% of the PVX signal was from the colon, mammary and brain tumor tissues, remaining particles were cleared by the reticuloendothelial system organs (the spleen and liver), followed by slower processing and clearance through the kidneys and bile. Original submitted 7 November 2012; Revised submitted 19 January 2013; Published online 9 July 2013